Oxygen microprofiles in natural seawater (Filtered, sea surface microlayer added, after 30 min) - Adenike Adenaya; Michaela Haack; Christian Stolle; Oliver Wurl; Mariana Ribas-Ribas (PANGAEA, 2021)
Oxygen microprofiles of de-ionised water and natural seawater were measured in a laboratory experiment in the marine interface lab at the Institute for Chemistry and Biology of the Marine Environment (ICBM), University of Oldenburg, in Wilhelmshaven, Germany, between November 2017 and November 2019. With the de-ionised water experiment, we added Oleyl achohol and Triton-X-100 and with the seawater, we measured filtered and unfiltered seawater and we added natural sea surface microlayer. For all the experiments we did three replicates of 30, 60 and 120 minutes waiting time. The oxygen concentrations were measured using a Clark-type OX-50 microsensor (Unisense, Denmark) connected to a picoammeter (Unisense Microsensor Multimeter, Denmark). The seawater samples were collected between November 2017 and November 2019 in the Jade Bay from the harbour close to the ICBM (Alter Vorhafen 53° 30 extquotesingle 49.4634" N 8° 8 extquotesingle 43.764" E). The different microprofiles were collected to calculate the diffusive boundary layer and how the articial and natural surfactants affect it. Sea surface microlayer samples were collected with the glass plate method. The glass plate (30 x 40 cm) was immersed vertically down into the underlying water and then withdrawn with approximately 5 cm per second up to allow the SML adhere to the glass plate based on capillary forces. The attached SML sample was then transferred into a sterile brown bottle from the glass plate with a squeegee. The glass plate was cleaned with 70 % ethanol before use and the process was repeated until required volume (100 mL) was obtained.
In: Adenaya, A et al. (2021): Oxygen microprofiles in de-ionised water and natural seawater [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.937780